ANALISIS TINGKAT KERAWANAN LONGSOR MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (SIG) PADA KECAMATAN TOMOHON BARAT DAN UTARA KOTA TOMOHON PROVINSI SULAWESI UTARA - Luntungan, P. B. G.; Rachmadhan, H.D.; Tandipajung, J. (LPPM Universitas PRISMA, 2023)
Natural disasters are natural events that can occur anywhere and at any time, causing material and material losses immaterial to people's lives. Landslides are one of the natural disasters that generally occur in mountainous areas, especially in the rainy season. West and North Tomohon sub-districts are areas that have the potential to experience landslides because the morphology of North and West Tomohon District varies, such as highlands, mountains and hills. One of The way that can be applied to estimate landslide disasters is to use an application that is able to take inventory affected locations, namely geographic information systems that have the ability to store, process, analyze andpresents geographically referenced data. In this research, soil vulnerability analysis was carried out using the weighting method and Scoring. The creation of this landslide susceptibility map is the result of overlaying secondary data such as DEM, cover maps land, rainfall data, regional geological maps, and soil type maps. Determining the level of landslide vulnerability is carried out by: multiplying the score by the weight for each parameter and then adding up the results for age. The value is classified into 4 landslide-prone zones, namely low, medium, high and very high. This research produces a landslide prone zoning map divided into 3 classes of vulnerability, namely medium class in Woloan Village, high class in Kaskakasen and Kayawu Village and Very high class in Taratara and Kinilow Villages. Based on five factors that influence landslide disasters, bulk factors Rain has the highest score which is the most dominant factor in influencing the occurrence of landslides. ResultsIt is hoped that the research carried out can be used as basic information for disaster mitigation, andregional development